Essays on Kant - Allison, Henry E. (Oxford : Oxford University Press, 2012)
This volume presents 17 essays by one of the world's leading scholars on Kant. Henry E. Allison explores the nature of transcendental idealism, freedom of the will and the concept of the purposiveness of nature. He places Kant's views in their historical context and explores their contemporary relevance to present day philosophers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Kant, Immanuel, -- 1724-1804.